Roles of Sub-District Administrative Organization in Preventing and Solving Drug Addiction In Youth: A Case Study Of Kungthanasarn Sub-District Administrative Organization, Phuviengdistrict, Khonkaen Province - Srisaardand, Vasant; Kittipanno, PhrmahaJaroon (Journal of Buddhist Education and Research (JBER), 2015)
The aims of this research were to study the role levels of the sub-district administrative organization in preventing and solving drug addiction in youth and to compare the opinions towards the roles the roles of the sub-district administrative organization in preventing and solving drug addiction in youth, the case study of Kungthanasarn Sub-District Administrative Organization, Phuvieng district, KhonKaen province, classified by background and differences. The quantitative research studied the samples selected by Taro Yamane method and accidental sampling. The tool used in this research was a questionnaire. The statistics used in data analysis were: Frequency, Percentage, Mean, Standard Deviation, t-test, f-test (One-way ANOVA) and Least Significant Difference. The research results were as follows: 1. The overall score of the role of Kungthanasarn Sub-District Administrative Organization was at a high level; each aspect consideration suggested that the aspect ‘public participation strategy’ had the highest score, followed by the strategy of drug and dealer control and the least was that of the strategy for creating and developing the system for receiving good persons to the society. 2. The population with differences in genders and occupations had their overall opinions on the roles of the sub-district administrative organization indifferently; while those with differences in age and education had their opinions towards the roles differently. 3. The highly recommendation for preventing and solving drug addiction in youth are that there should be support of youth development outside the educational institutions through a variety of activities such as work creation, career creation, non-formal education, sport/entertainment and volunteer activity by using the youth centre as the operational centre, followed by the sub-district administrative organization should support the project ‘TO BE NUMBER ONE’ in educational institutions in cooperation with local organizations. The least suggestion was that the sub-district administrative organization should make protection, inserted in learning and instructing of teachers and advisers by building knowledge and lifelong skills for drug prevention.